Knowledge and attitudes of nursing professionals regarding oral hygiene in critically ill patients - Adriana Maria da Silva Felix; Isabela Di Tilia Alves do Amaral; Regina Claudia Silva de Souza; Rosemeire Ângela de Queiroz Soares (Universidade Federal de Santa Maria, 2021)
Objective: to compare the knowledge and attitudes of nursing professionals working in public and private hospitals on oral hygiene in critically ill patients. Method: a cross-sectional study carried out in two adult Intensive Care Units, one public and the other one private, between the period of December 2018 and January 2019, using a structured and self-administered questionnaire. Results: the knowledge rate of professionals in the public hospital was 76.6% and the attitude was 62.7%, while in the private hospital, these rates were 81.8% and 67.1%, respectively. There were significant differences regarding the existence of a protocol (p 0.006), participation in training (p 0.004), and the use of a toothbrush with soft bristles and suction (p 0.001) in the private hospital. Conclusion: the knowledge level was higher, and the attitudes toward oral hygiene were more positive among nursing professionals at the private hospital compared to the professionals at the public hospital.